Rytą or ryte? Vakarą or vakare? A corpus analysis of Lithuanian time expressions denoting parts of the day - Kapušová, Nina (Kalbotyra, 2024)
This paper aims to reveal differences between the competing accusative and locative forms of Lithuanian temporal expressions denoting parts of the day (rytas ‘morning’, diena ‘day’, vakaras ‘evening’, naktis ‘night’). Since the accusative of time expresses a wider semantic spectrum, it was first necessary, using a prototypical approach, to define exactly what the morphosyntactic and semantic characteristics of the competing pairs are (i.e., prototypical verbal modifiers expressing location of an action/ state in time). Then, analysing the DLKT corpus data confirmed that the competition between the accusative and locative forms is present using the word vakaras ‘evening’ and rytas ‘morning’. This study reveals that the choice of case depends on the interaction of the given word with the (non)presence of an attribute and on the concrete type of attribute as well. It was confirmed that the accusatives of all the studied words predominate over the locatives, but the strength of the dominance varies. This may be caused by the different degree of adverbialization of the locative forms and by the different semantic implications embodied in the lexemes themselves, which is related to how successfully the locative resists the expansion of the accusative.